Marketing Strategy of Kretek Cigarettes “Semar Manthoel” Product PR. Yasin Jaya Abadi in Jember Regency - Wahyono, Nanang Dwi; Hasanah, Niswatin; Kustiari, Tanti (International Journal of Technology, Food and Agriculture, 2025)
PR. Yasin Jaya Abadi is a small-medium enterprise (SME) engaged in the production of kretek (clove) cigarettes in Jember Regency. Despite operating since 2021 with its flagship product “Semar Manthoel,” the company continues to face marketing challenges, relying solely on traditional methods such as word-of-mouth and limited social media use. This highlights a significant research gap regarding the effectiveness of marketing strategies among local kretek brands. This study aims to: (1) analyze internal and external factors influencing the company’s marketing performance, (2) formulate alternative marketing strategies, and (3) identify the most suitable priority strategy. Using IFE, EFE, SWOT, IE, and QSPM matrix analyses, the findings reveal that the most effective strategy is to enhance product characteristics and leverage a strategic location to reach a wider market, with the highest total attractiveness score (TAS = 7.625). This strategy significantly contributes to increasing market share and strengthening competitive positioning. The results offer valuable insights for SMEs in the tobacco sector seeking to improve marketing effectiveness and sustainability in a highly competitive industry.